Research on the Current Situation and Influencing Factors of Professional Identity of Sports Major Students from the Perspective of College Youth Subculture - Chen, Shan (Education Insights, 2026)
This study takes 90 sports majors in Wuhan Institute of physical education as the research object, and uses the methods of questionnaire, mathematical statistics and interview to explore the current situation and core influencing factors of Sports Majors’ professional identity from the perspective of youth subculture in Colleges and universities. The results show that professional interest, teachers’ teaching attitude, professional recognition willingness, family support and good learning attitude are the five key factors affecting the professional identity of sports majors; Personal factors (43%) accounted for the largest proportion of professional identity, followed by teaching factors (35%) and social and family factors (22%), and professional interest was the core driving factor. Teachers’ teaching attitude and family support were significantly positively correlated with students’ professional identity. Based on the research results, this paper puts forward targeted suggestions from the three levels of individual, school and family, in order to improve the professional identity level of sports major students and reduce the negative impact of bad youth subculture in Colleges and universities.